(untitled) (Global Journal of Human-Social Science, 2018)
The article deals with the problem of determination, maintenance and inventor activity of world aviation developers. They were born in Ukraine, as real cradle of aviation specialists having trained thousands of experts, which have been working in Ukraine and in almost 90 countries over the world. Planes and gliders, developed in Ukraine set world records.